2013
DOI: 10.1186/1756-8722-6-33
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric antigen receptor containing ICOS signaling domain mediates specific and efficient antitumor effect of T cells against EGFRvIII expressing glioma

Abstract: BackgroundAdoptive transfer of chimeric antigen receptor (CAR)-modified T cells appears to be a promising immunotherapeutic strategy. CAR combines the specificity of antibody and cytotoxicity of cytotoxic T lymphocytes, enhancing T cells’ ability to specifically target antigens and to effectively kill cancer cells. Recent efforts have been made to integrate the costimulatory signals in the CAR to improve the antitumor efficacy. Epidermal growth factor receptor variant III (EGFRvIII) is an attractive therapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(47 citation statements)
references
References 23 publications
1
46
0
Order By: Relevance
“…CAR T cells with ICOS domains retain a "bipolar" bias toward a T H 1 and T H 17 signature, which is a plasticity that appears to be a prerequisite for potent antitumor activity in several preclinical models. 17 Shen et al constructed an ICOS-based CAR that recognizes EGFRvIII, 33 and demonstrated that T H 1 cells redirected with this CAR could release IFN-g and destroy glioma cells in an antigen-dependent manner. Our results confirm and extend this work by performing a comprehensive analysis of CARs expressing ICOS signaling domains.…”
Section: Programming T H 17 Cells With Icos-based Cars 1077mentioning
confidence: 99%
“…CAR T cells with ICOS domains retain a "bipolar" bias toward a T H 1 and T H 17 signature, which is a plasticity that appears to be a prerequisite for potent antitumor activity in several preclinical models. 17 Shen et al constructed an ICOS-based CAR that recognizes EGFRvIII, 33 and demonstrated that T H 1 cells redirected with this CAR could release IFN-g and destroy glioma cells in an antigen-dependent manner. Our results confirm and extend this work by performing a comprehensive analysis of CARs expressing ICOS signaling domains.…”
Section: Programming T H 17 Cells With Icos-based Cars 1077mentioning
confidence: 99%
“…In the context of adoptive immunotherapy, ICOS signaling enhances the antitumor activity of human and murine Th17 cells and Tc17 cells (9,51). Moreover, introducing the ICOS domain into CARs enhanced cellular engraftment in vivo (52)(53)(54). In light of our work, we suspect that combining drugs or genetic strategies to regulate p110δ and β-catenin induced in T cells could augment various forms of cancer immunotherapy, including cytokine therapy, checkpoint modulators, and cellular therapy.…”
Section: Discussionmentioning
confidence: 76%
“…First-generation CARs include only immunoreceptor tyrosine-based activation motifs (ITAMs) from the CD3ζ chain or the FcR-γ chain as an intracellular signaling domain [8], whereas second-generation CARs include a single costimulatory domain derived from CD28 [42,43], CD134 (OX40) [44], CD137 (4-1BB) [45,46], CD27 [47], or inducible costimulator (ICOS) [48,49], and third-generation CARs include 2 or more costimulatory domains in addition to the CD3ζ chain or FcR-γ chain [50,51].…”
Section: Car Signalingmentioning
confidence: 99%